Public Perception of Trust in the Legal System Based on Viral Legal Cases on Various Media in Indonesia - Mesra, Romi; Lasut, Meiske; Nasirun, Indrasatya Octavianus (PT. NALURI EDUKASI PRESS, 2024)
This research aims to investigate public perceptions of trust in the Indonesian legal system based on an analysis of three legal cases that went viral in various media. The cases selected were the Case of Brigadier J or Ferdy Sambo, the Case of Mario Dandy and the Son of a Tax Official, and the Corruption Case of the Ministry of Agriculture, Syahrul Yasin Limpo. This research uses a qualitative approach with literature study data collection methods. Data was obtained from news sources, articles, media reports, and related research that discussed these three cases. Analysis was carried out to identify general patterns, public perceptions, and implications for trust in the legal system. The research results show that the Brigadier J case raises doubts about the justice of the legal system, while the case of Mario Dandy and the Tax Official's Son strengthens perceptions about abuse of power and privilege, the Ministry of Agriculture corruption case shows the negative impact of corruption on public trust in the government and the legal system. The public feels injustice and a lack of trust in the integrity of the legal system, which can threaten the legitimacy of legal institutions.